Robust Proportional Integral-State Feedback with Disturbance Observer for 2-DOF Helicopter System - Abd Al Kareem Mohammed, Shatha; Hussien Mary, Ali; Al‐Abadi, Ali; Ghufran Khidhir Abboosh, Mohammed (Al-Khwarizmi Engineering Journal, 2024)
This paper presents a new optimal robust control algorithm based on a proportional-integral (PI) and state feedback controller with a state disturbance observer for the two degrees-of-freedom helicopter system. A disturbance observer is used to improve the robustness of the proposed controller instead of using high gain to reject the external disturbance. Combining the PI controller with the state feedback controller improved the performance of the controlled system. Simulations based on Matlab 2022 are performed to compare the proposed controller with the linear quadratic regulator controller and investigate the performance and robustness of the proposed control method. The comparison between controllers was made under three cases: 1) nominal model, 2) disturbance rejection and 3) system uncertainty. The proposed algorithm shows good performance, which was confirmed clearly by the simulation results that illustrate the transient specifications represented by no overshot, the smallest settling time, and the smallest integral square error. The algorithm also indicates a good choice of objective function based on the infinity norm of the transfer function to ensure high robustness regardless of the external disturbance and parameter variations in the system.